Detection of Mycoplasma genitalium in female cervical samples by Multitarget Real-Time PCR - Sabina Mahmutović-Vranić; Edina Bešlagić; Justin Hardick; Maida Šlaković; Charlotte A. Gaydos (Biomolecules & Biomedicine, 2007)
Mycoplasma genitalum (MG) is associated with variety of urogenital infections such as non-gonococcal urethritis (NGU), endometritis and cervicitis. The objective of this study was to demonstrate and evaluate a research polymerase chain reaction (PCR) assay, for the detection of MG in cervical samples of a tested population of women attending gynecology clinics in Bosnia and Herzegovina. The Multitarget Real-Time (MTRT) PCR, utilizing the ABI 7900HT, the sequence detection system, was performed for the detection of MG. Cervical samples (N=97) from females were divided into three types of patient groups: Group 1: patients who had known abnormal clinical cytology reports (N=34); Group 2: patients who reported a history of genitourinary infections (N=22); and Group 3: patients not in either groups 1 or 2 (N=41). Overall, 14,43% (14/97) of those tested were positive for MG. A positive sample was defined as having a cycle threshold cross point (Ct) < 40,0 with a fluorescent detection comparable to the low positive control utilized during the run. This study validated the use of MTRT PCR as a reliable method for the detection of MG in clinical specimens and should facilitate large-scale screening for this organism.